Pulmonary Actinomycosis Appearing as Carcinoma - Nilay Cavusoglu Yalcin, Muharrem Özkaya; Kizilates, Filiz (International Journal of Innovative Research in Medical Science, 2017)
Background: Actinomycosis is a rare and chronical pulmonary infection caused by Actinomyces species, normally colonized in the mouth and gastrointestinal tract of human. Pulmonary involvement represents approximately 15% of all cases. We decribe herein a case of pulmonary actinomycosis, appearing as carcinoma and diagnosed in pathological examination. Case presentation: A 47-years old immunocompetent male patient who had cough and hemoptysis, was considered in emergency department of Antalya Training and Research Hospital. He had a history of bronchoscopy with non-diagnostic results in another healthcare center. In chest computerized tomography, a mass lesion with a diameter of six centimeter in the medial basal segment of right lower lobe of lung. The patient underwent diagnostic and therapeutic thoracotomy and by the pathological examination of the resected specimen, the patient was diagnosed as pulmonary actinomycosis. Conclusion: Pulmonary actinomycosis is a rare disease but physicians have to be aware that actinomycosis may mimic the malignancy and it should be kept in mind when a middle-aged male patient presents with hemoptysis and cough together with the radiological findings of a peripheral mass or chronic consolidation.